The complementarity of academic and commercial research output in funded research teams: evidence from a survey of publicly funded Irish researchers. (2018) - Bourke, Jane; Jordan, Declan
Using data from a census of Science Foundation Ireland (SFI) funded researchers, this paper explores the determinants of academic and commercial research outputs in publicly funded research teams. Using a conditional mixed process model, the paper estimates the effect on research output of national and international academic collaboration, industry collaboration and team size on research outputs. The paper also examines the extent to which academic and commercial research outputs are complements or substitutes. The paper finds that collaboration with both domestic and international academics increases the likelihood of academic research outputs. Interaction with SMEs and MNCs increases the likelihood of academic research outputs, but has no direct effect on commercial research outputs. There is evidence of a complementary relationship between academic and commercial outputs. This suggests that greater emphasis on commercial impact for funded research is not at the expense of lower bibliometric output.